Adaptable integrated sensing and communication for UAV‐empowered 6G networks - Yan Yang; Jianwei Zhao; Feifei Gao; Weimin Jia; Di Mu (Electronics Letters, 2024)
Abstract Integrated sensing and communication (ISAC) is a promising technique for unmanned aerial vehicle‐empowered 6G networks. This letter proposes a novel, adaptable ISAC mechanism. Firstly, both the communication and sensing channel models under the Doppler and beam‐squint effects are investigated. Then, an adaptive sensing method is proposed by the joint design of signal echo sensing and beam‐squint sensing under practical environment. Specifically, when the echo power is larger than the minimum detectable power, the proposed method could realize the effective sensing by utilizing the system model without feedback. Otherwise, the proposed method could exploit the beam‐squint for sensing with the feedback of the sub‐carrier index. Finally, various simulation results are provided to demonstrate the effectiveness of the proposed scheme.